2005
DOI: 10.1111/j.1523-1755.2005.00608.x
|View full text |Cite
|
Sign up to set email alerts
|

Variation in the serum creatinine assay calibration: A practical application to glomerular filtration rate estimation

Abstract: Recalibration of serum creatinine assays to the MDRD Study clinical laboratory would improve accuracy of GFR estimation using the MDRD Study equation, but is not practical for all clinical laboratories. As an interim solution, clinical laboratories could report GFR estimates <60 mL/min/1.73 m(2) without recalibration with an acceptable accuracy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
95
1
3

Year Published

2007
2007
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(99 citation statements)
references
References 14 publications
0
95
1
3
Order By: Relevance
“…The impact of the calibration on the MDRD results is far from negligible, especially in the high GFR range [7,9,[17][18][19]. The MDRD study equation has even been modified to be useful with IDMS traceable creatinine [13,15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The impact of the calibration on the MDRD results is far from negligible, especially in the high GFR range [7,9,[17][18][19]. The MDRD study equation has even been modified to be useful with IDMS traceable creatinine [13,15].…”
Section: Discussionmentioning
confidence: 99%
“…The calibration of sCr methods improved the accuracy of GFR estimation and Murthy et al recommended that the GFR would be estimated below 60 mL/min/1.73 m 2 only, unless the method has been calibrated [9].…”
Section: Introductionmentioning
confidence: 99%
“…While, extensive evaluation of the MDRD Study equation showed good performance in populations with lower levels of GFR but variable performance in those with higher levels [17]. Variability among clinical laboratories in calibration of Scr assays [18] introduces error in GFR estimates, especially at high levels of GFR [19]. Thus, the National Kidney Disease Education Program (NKDEP) has initiated a creatinine standardization program to improve and normalize Scr results used in estimating equations [14].…”
Section: Discussionmentioning
confidence: 99%
“…Underestimation of higher GFR levels with overestimation of CKD has been observed [3]. Underestimation of iGFR has been attributed to inaccuracies of measurement, and greater variability in creatinine concentration due to non-renal factors in patients without CKD [4][5][6].…”
Section: Discussionmentioning
confidence: 99%
“…Serum creatinine is a critical variable for MDRD-calculated eGFR. Currently great interlaboratory variability exists in the measurement and calibration of creatinine [4,5]. This variability introduces error into GFR estimates, which has greatest impact at creatinine concentrations within the normal range; this is particularly important when attempting to detect early decline in GFR [4].…”
Section: Introductionmentioning
confidence: 99%